2007
DOI: 10.1093/ser/mwl035
|View full text |Cite
|
Sign up to set email alerts
|

Contradiction, convergence and the knowledge economy: the confluence of academic and commercial biotechnology

Abstract: Efforts to understand the structure of the emerging knowledge economy have paid particular attention to the shifting boundary between academic and commercial (for-profit) research, especially in life sciences. Yet, empirical studies have tended to adopt a segmented approach, focusing on either industry or the academy, thus obscuring the increasingly interwoven nature of these two domains. In this paper, we explore the changing organizational logics that govern both academic and corporate science, using intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
127
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(132 citation statements)
references
References 56 publications
(53 reference statements)
3
127
0
2
Order By: Relevance
“…For example, Haeussler (2011) found that for both academic and industrial scientists the likelihood of collaboration and exchange depends on the competitive value of the requested information and on the degree to which the researcher's community conforms to the 'norm of open science' (Rhoten and Powell 2007). Differences between academic and industrial research become blurred (Vallas and Kleinman 2008). Thus, academic and industrial science moved from a ''binary system of public vs. proprietary science to […] arrangements which combine elements of both'' (Rhoten and Powell 2007, p. 346).…”
Section: Perspectives Of Open Sciencementioning
confidence: 99%
“…For example, Haeussler (2011) found that for both academic and industrial scientists the likelihood of collaboration and exchange depends on the competitive value of the requested information and on the degree to which the researcher's community conforms to the 'norm of open science' (Rhoten and Powell 2007). Differences between academic and industrial research become blurred (Vallas and Kleinman 2008). Thus, academic and industrial science moved from a ''binary system of public vs. proprietary science to […] arrangements which combine elements of both'' (Rhoten and Powell 2007, p. 346).…”
Section: Perspectives Of Open Sciencementioning
confidence: 99%
“…Lately there has been increasing concern in academic literature about the growing ties between industry and the academic research community [1][2][3][4][5][6]. For example, there is emerging evidence that these relationships can increase information withholding among researchers [7][8][9][10], skew the direction of research results toward findings supportive of industry sponsors [8,9,11], alter the tone of popular representations of research [12] and, perhaps most importantly, erode public trust in the research and researcher [13,14].…”
mentioning
confidence: 99%
“…It is thus important to pay attention to the multiplying demands (cf. Vallas and Kleinman, 2008;Tuunainen, 2005b;Owen-Smith and Powell, 2002) scientists have to deal with in their day-to-day work in order to gain a richer understanding of scientifi c work under increasing commercialization pressures. However, this should not only include scientists' attitudes towards commercialization pressures, but, importantly, also the practices by which they 'make it work' despite the potential for confl ict.…”
Section: Resultsmentioning
confidence: 99%
“…For example, scientists display varying attitudes concerning engagement with corporate or policy actors, ranging from advocating engagement to outright resistance (Goldstein, 2010;Holloway, 2015;Lam, 2010;Owen-Smith and Powell, 2002). What seems to account for the variety of attitudes among scientists is the fact that the current ecology of academic knowledge production is one of multiplying contradictory regimes, logics, or social worlds (for different takes on the theme of multiplicity, see Miller, 2001;Owen-Smith and Powell, 2002;Tuunainen, 2005b;Vallas and Kleinman, 2008).2 On the individual level, tensions resulting from confl icting social worlds may be experienced by scientists as considerable 'role-strain' (Boardman & Bozeman, 2007).The bulk of the literature has emphasized how organizations manage such tensions on an administrative level, emphasizing a struggle over resources. In the case of private companies using university resources ('hybrid fi rms'), tensions may be managed through geographical or physical separation and formal redistribution of academic and corporate roles and resources in an attempt to maintain what are perceived as traditional cultural boundaries (Tuunainen, 2005a(Tuunainen, , 2005bTuunainen and Knuuttila, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation